Release of an encrypted, highly potent ACE-inhibitory peptide by enzymatic hydrolysis of moth bean (Vigna aconitifolia) protein - Goyal, Nancy; Hajare, Sachin N.; Gautam, Satyendra (Frontiers in Nutrition, 2023)
Aim Dietary approaches for the regulation of blood pressure are the need of the hour. Hence, identifying the foods possessing such activity is gaining importance. With this aim, moth bean (Vigna aconitifolia), an underutilized pulse, was explored for the presence of antihypertensive activity in terms of angiotensin converting enzyme (ACE)-inhibition bioactivity. Methods Defatted moth bean protein concentrate was hydrolyzed by using different proteases including Alcalase, papain, and trypsin, to identify the enzyme producing highly potent ACE inhibitory peptides. The hydrolysate showing the highest ACE inhibitory activity was further fractionated using an ultrafiltration membrane (10, 3 and 1 kDa) based on ACE inhibitory activity. The active fraction was further subjected to the ion-exchange chromatography followed by RP-HPLC and LC-MS/MS analysis for the enrichment and identification of ACE inhibitory peptides. Finally, based on the bioinformatic analysis, few peptides were synthesized and evaluated for ACE inhibitory activity, followed by docking study and molecular dynamic simulation of a peptide with the highest ACE inhibitory activity. Results and discussion Out of the three proteases, Alcalase-derived hydrolysate showed the highest ( 59%) ACE inhibition activity. Molecular weight-based fractionation revealed that <1 kDa fraction possessed the highest ACE inhibitory activity. Activity guided separation of 1 kDa fraction using ion-exchange chromatography, RP-HPLC and LC-MS/MS showed the presence of about 45 peptides. Based on the bioinformatic analysis, 15 peptides were synthesized and evaluated for ACE inhibitory activity. Among these, a novel octapeptide FPPPKVIQ showed the highest ACE inhibitory activity (93.4%) with an IC50 of 0.24 μM. This peptide retained about 59% activity post gastrointestinal digestion simulation. A Dixon plot as well as docking studies revealed the uncompetitive inhibitory nature of this peptide with a Ki value of 0.81 μM. Molecular dynamic simulation studies till 100 ns ensured the stability of the ACE-peptide complex. Conclusion Thus, present study identified a novel potent ACE inhibitory peptide from moth bean that can be incorporated in a functional dietary formulation for regulation of hypertension.